Bridging the cultural gap in Bible translation as a case in point - C. Nord (Acta Theologica)
Translation practitioners have always been aware of the fact that translation is not a purely linguistic operation but a means of facilitating communication between members of different cultures. Translation scholars have only recently discovered this fairly obvious aspect of their field - and the functional approach to translation — or skopos theory — was instrumental in turning it into one of the main concerns of modern translation studies. New Testament and early Christian texts refer to a culture from which we are separated by a huge cultural gap. They have been translated and re-translated many times during the past (almost) 2000 years and into almost all languages on the planet. In spite of that, we do not always feel that the cultural gap has really been bridged. Does this justify yet another translation? Together with my husband, Klaus Berger, who is a New Testament scholar at Heidelberg University, I was engaged in a fascinating project: We translated the texts of the New Testament plus a large number of apocrypha from the original Greek (and Latin, Syriac, Coptic, Ethiopic, and Arabic) into German. It was the first translation of these texts that involved a theologian and a translation scholar, and it was the first translation based on modern functional translation theory. Using a few examples from our translation and comparing them to several translations into other modern languages (such as Afrikaans, English, and French), I would like to show how we went about in order to bridge the cultural gap, making the texts  understandable to modern German readers without taking away their strangeness.